User satisfaction adaptive behaviors for assessing energy efficient building indoor cooling and lighting environment - Keyvanfar, Ali (Elsevier, 2014)
Many techniques for managing sustainability including sustainable building assessment tools and standards have been developed globally. The sustainable building assessment tools measure the user satisfaction dependent to environmental and economic aspects of energy efficient building practices. However, these tools have not yet measure energy efficiency index by involving user satisfaction from adaptive behaviors dependently, which can determine the actual energy consumption versus the planed energy consumption of the building. Hence, this research aimed at providing a comprehensive list of adaptive behaviors for assessing energy efficient building indoor environment in design phase of building lifecycle. The study focused on identifying and establishing adaptive behaviors that are in response to indoor conditions provided by Cooling and Lighting systems in energy efficient office buildings. This research involves adaptations across Technological and Personal. The research was conducted in two phases. Phase one identified the list of user satisfaction adaptive behaviors through a systematic approach. Next, an expert input study was conducted to validate the findings of the literature review. Expert input data was collected using Delphi structured close group discussion method, and then analyzed through Grounded Group Decision Making (GGDM) method. Eight experts were involved in four sessions of the GGDM application procedure. The research established 18 adaptive behaviors relevant to cooling system in energy efficient indoor environments, and 18 adaptive behaviors relevant to the lighting system. The comprehensive list of user satisfaction adaptive behaviors can be applied in both current and future sustainable building assessment tools energy efficiency indexes. This aids architects, engineers, facility managers, building owners, consultants, authorities, contractors, and academic researchers in accreditation of building users, building design and reduction of buildings energy consumption.